2020
DOI: 10.1093/ons/opaa163
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Supraclavicular Versus Video-Assisted Intrathoracic Phrenic Nerve Section for Transfer in Patients With Traumatic Brachial Plexus Injuries: Case Series

Abstract: BACKGROUND The phrenic nerve has been extensively reported to be a very powerful source of transferable axons in brachial plexus injuries. The most used technique used is supraclavicular sectioning of this nerve. More recently, video-assisted thoracoscopic techniques have been reported as a good alternative, since harvesting a longer phrenic nerve avoids the need of an interposed graft. OBJECTIVE To compare grafting vs phreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…We found a similar study published recently which concluded that supraclavicular PN transfer had better results compared to VATS aided PN transfer for restoration of elbow flexion in brachial plexus injuries. 19 However, this study was a comparison made between two medical centers and it was not mentioned if the surgeons’ level of expertise were comparable. There were too many variables for target nerve coaptation in supraclavicular PN transfer group and some were sutured directly without nerve graft.…”
Section: Discussionmentioning
confidence: 99%
“…We found a similar study published recently which concluded that supraclavicular PN transfer had better results compared to VATS aided PN transfer for restoration of elbow flexion in brachial plexus injuries. 19 However, this study was a comparison made between two medical centers and it was not mentioned if the surgeons’ level of expertise were comparable. There were too many variables for target nerve coaptation in supraclavicular PN transfer group and some were sutured directly without nerve graft.…”
Section: Discussionmentioning
confidence: 99%
“…If the anterior division of the upper trunk is unaffected, a direct nerve transfer of the phrenic nerve via supraclavicular approach to the anterior division of the upper trunk could be performed. However, this procedure may be associated with axonal misrouting caused by choosing a too proximal target [ 15 ]. Thus, a direct phrenic nerve transfer to the musculocutaneous nerve is certainly preferable.…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative systematic review by Cardoso et al [ 9 ] showed that elbow flexor muscle strength had been graded ≥ M3 (movement against gravity is just possible) according to the British Medical Research Council scale [ 10 , 11 ] in 70.1% of patients following phrenic nerve transfer to the musculocutaneous nerve. Phrenic nerve transfer to the musculocutaneous nerve can be achieved by means of video-assisted thoracic surgery without nerve graft [ 3 , 5 , 9 , 12 , 13 , 14 , 15 ] or via supraclavicular approach in combination with an autograft [ 12 , 15 , 16 ]. It could be shown in a recent study that patients who underwent supraclavicular sectioning of the nerve in combination with an autograft had a significantly better clinical outcome (elbow flexion strength recovery) compared to patients treated by video-assisted thoracoscopic technique without nerve autograft [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The ICN-MCN transfer was the preferred choice for elbow flexion reconstruction in total or C5-8 types of BPI because of limitations in alternative NTs such as phrenic NTs with postoperative pulmonary complications and inconsistent recovery results after contralateral C7 root transfer. 3 , 4 , 5 , 6 …”
mentioning
confidence: 99%